2020
DOI: 10.1038/s41598-020-66628-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a natural disaster on access to care and biopsychosocial outcomes among Hispanic/Latino cancer survivors

Abstract: Cancer is the leading cause of death in Puerto Rico (PR). Hurricane Maria (HM) and its aftermath lead to widespread devastation on the island, including the collapse of the healthcare system. Medically fragile populations, such as cancer survivors, were significantly affected. The goal of this study was to assess the impact of HM on barriers to care, emotional distress, and inflammatory biomarkers among cancer survivors in PR. This exploratory longitudinal study was conducted in health care facilities and comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
0
13
0
2
Order By: Relevance
“…Our findings are consistent with a recent study conducted in PR with 41 matched cancer survivors and non-cancer patient pairs. 26 That study found that cancer survivors experienced more barriers to access medical care compared to non-cancer patients, especially in the first 6 weeks after Hurricane Maria. 26 Patients in our study said that disruptions in cancer care were mostly caused by damage to health care infrastructure and loss of utility services.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with a recent study conducted in PR with 41 matched cancer survivors and non-cancer patient pairs. 26 That study found that cancer survivors experienced more barriers to access medical care compared to non-cancer patients, especially in the first 6 weeks after Hurricane Maria. 26 Patients in our study said that disruptions in cancer care were mostly caused by damage to health care infrastructure and loss of utility services.…”
Section: Discussionmentioning
confidence: 93%
“… 26 That study found that cancer survivors experienced more barriers to access medical care compared to non-cancer patients, especially in the first 6 weeks after Hurricane Maria. 26 Patients in our study said that disruptions in cancer care were mostly caused by damage to health care infrastructure and loss of utility services. Their experiences align with findings from a recent systematic review showing that electricity and water supply are often damaged when hurricanes hit, leading to service disruption in cancer care facilities, resulting in extended closure of units and subsequent oncology treatment delays.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent literature shows that one of the primary concerns of cancer patients following a natural disaster is access to treatment [ 18 ]. Moreover, a study conducted on cancer patients showed that Hurricane Maria caused long-lasting effects on barriers to health care [ 19 ]. This data supports the need for investment in healthcare infrastructure to ease access to health care after a natural disaster.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Puerto Rico measured the impact of a Category 4 hurricane on barriers to care, emotional distress, and inflammatory biomarkers among cancer patients. 45 Barriers in accessing medical care were directly associated with perceived stress, anxiety, and post-traumatic symptomatology, and to increased levels of inflammatory cytokines. Our team has recently demonstrated that stress increases the size of endometriosis lesions and inflammation using a rat model, further proving that stress plays a key role in disease progression.…”
Section: Discussionmentioning
confidence: 99%